(untitled) - Bligh, Philip (Hoboken, N.J., 2004)
Building and maintaining a customer-centered enterprise cost-effectively is a hot topic and key business issue. This book provides the definitive work on how to derive return from investment. It answers the question: What is the real benefit of customer ERP? By knowing this answer corporations can avoid being disappointed with their implementation
Keywords: Customer relations,Customer relations,Quan hệ khách hàng,Quan hệ khách hàng; Management,Management,Data processing,Quản lý,Quản lý,Xử lý dữ liệu